2012
DOI: 10.1042/bst20120051
|View full text |Cite
|
Sign up to set email alerts
|

SRPK1 inhibition in vivo: modulation of VEGF splicing and potential treatment for multiple diseases

Abstract: SRPK1 (serine-arginine protein kinase 1) is a protein kinase that specifically phosphorylates proteins containing serine-arginine-rich domains. Its substrates include a family of SR proteins that are key regulators of mRNA AS (alternative splicing). VEGF (vascular endothelial growth factor), a principal angiogenesis factor contains an alternative 3' splice site in the terminal exon that defines a family of isoforms with a different amino acid sequence at the C-terminal end, resulting in anti-angiogenic activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 44 publications
1
46
0
1
Order By: Relevance
“…25 We show here that diabetic patients with well preserved kidney function have increased VEGF-A 165 b levels relative to VEGF-A 165 a. Transgenic podocyte-specific VEGF-A 165 b overexpression is the most analogous experimental model of this human situation, and it is noteworthy that the local upregulation of VEGF-A 165 b was the most effective approach in preventing multiple physiologic and histologic changes of diabetic nephropathy. We hypothesize that patients capable of upregulating VEGF-A 165 b relative to VEGF-A 165 a, via the modifiable machinery that regulates alternative splicing of the VEGF-A gene, 23,[26][27][28][29] may be protected from progressive nephropathy in diabetes. How to manipulate this alternative splicing mechanism for therapeutic benefit requires further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…25 We show here that diabetic patients with well preserved kidney function have increased VEGF-A 165 b levels relative to VEGF-A 165 a. Transgenic podocyte-specific VEGF-A 165 b overexpression is the most analogous experimental model of this human situation, and it is noteworthy that the local upregulation of VEGF-A 165 b was the most effective approach in preventing multiple physiologic and histologic changes of diabetic nephropathy. We hypothesize that patients capable of upregulating VEGF-A 165 b relative to VEGF-A 165 a, via the modifiable machinery that regulates alternative splicing of the VEGF-A gene, 23,[26][27][28][29] may be protected from progressive nephropathy in diabetes. How to manipulate this alternative splicing mechanism for therapeutic benefit requires further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28] Several studies have shown the involvement of various members of splicing kinases, especially SRPKs in multiple cellular processes including proliferation and angiogenesis. 29,30 Overexpression of splicing factors (SRSF1, SRSF2) has been reported in lung, colon and breast cancers.…”
Section: Discussionmentioning
confidence: 99%
“…54,55 The lower availability results in alterations in AS of specific genes regulated by MBNL, which contribute to myotonic dystrophy pathogenesis. SRPK1, a kinase that phosphorylates SR-proteins (the class of splice factors mentioned above), is overexpressed in several cancers [56][57][58] and also in DenysDrash syndrome, associated renal failure, and increased incidence of Wilms tumors. 59 SRPK1 is a determinant of angiogenesis through modulation of VEGF-A splicing and its abnormal expression maintains a pathologic loop by promoting proangiogenic and propermeability VEGF-A isoforms.…”
Section: Splice Factors or Splicing-specific Kinases Are Deregulated mentioning
confidence: 99%